Performance study and analysis between vector control and direct power control for DFIG based wind energy system - Gufran Nurettin; Ata Sevinç (International Journal of Energetica)
This paper concentrates on analyzing the performance of the two most important techniques of independent active and reactive power control of the doubly-fed induction generator used in a variable speed wind power conversion system. In the first technique, the independent control of the active and reactive power is based on the vector control technique by the orientation of the stator voltage space vector using PI controllers; the decoupling components are deduced along with the d, q axes; and the PI controllers' parameters are calculated from the mathematical model of the doubly-fed induction generator. Hysteresis controllers are utilized to designing a direct power control technique. The performances of the studied control methods are tested and compared via simulation results.